KAJIAN PEMANFAATAN TEPUNG AMPAS KELAPA SEBAGAI CAMPURAN PAKAN UNTUK IKAN LELE DUMBO, Clarias gariepinus (Burchell, 1822) - Wulandari, Wulandari; Yudha, Indra Gumay; Santoso, Limin (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Coconut waste is one of the industrial waste or household waste that potentially can be mixed in feed, because it contains of 5,7% protein, 16,3% fat, 38,1% carbohydrate, 31,6% rough fiber, 5,5% water, and 2,6% ash. The aim of this study was to learn the effectivity of adding shredded coconut waste as fish feed ingredients for dumbo catfish fry. This research was carried out in 60 days in Aquaculture laboratorium, Fisheries and Marine, Agriculture Faculty, University of Lampung. This research used completety randomized design with 4 treatments and 3 repetitions. Treatment A (0% of coconut waste flour), treatment B (10% of coconut waste flour), treatment C (20% of coconut waste flour), and treatment D (30% of coconut waste flour). The parameters in this research were growth rate, daily growth rate, and feed conversion ration and protein retention and water quality. The result showed that the use of coconut waste flour in feed gave no effect to the growth rate, daily growth rate, and feed conversion ratio for the dumbo catfish.